2020
DOI: 10.3389/fimmu.2020.02040
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of AdipoR1 in Regulating Th17 Cell Differentiation Through Modulation of HIF-1α-Dependent Glycolysis

Abstract: We previously reported that adiponectin (AD) promotes naïve T cell differentiation into Th17 cells and participates in synovial inflammation and the bone erosion process in patients with rheumatoid arthritis. Here, we use a T cell lineage adiponectin receptor 1 (AdipoR1) conditional knockout model to investigate the role of AdipoR1 in Th17 differentiation. RNA-sequencing (RNA-seq) demonstrated that AdipoR1 knockout reduced the expression of a variety of T cell related genes, with Rorc showing the greatest leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
(35 reference statements)
0
23
0
Order By: Relevance
“…HMW adiponectin induced the production of IL-6 in unstimulated but not LPS-activated human monocytes, while LMW reduced IL-6 and increased IL-10 in LPS-activated monocytes [ 55 ]. Adiponectin seems to promote the differentiation of naïve T cells into Th17 cells, contributing to synovial inflammation and bone erosions, which may be mostly dependent on AdipoR1, demonstrated in conditional AdipoR1 knockout models [ 56 ]. Other cell types such as chondrocytes, endothelial cells, and lymphocytes also showed a pro-inflammatory response to adiponectin [ 12 , 24 ], suggesting a mainly pro-inflammatory effect of adiponectin locally within the affected joints ( Figure 1 ).…”
Section: Adipokines In Autoimmune Rheumatoid Arthritismentioning
confidence: 99%
“…HMW adiponectin induced the production of IL-6 in unstimulated but not LPS-activated human monocytes, while LMW reduced IL-6 and increased IL-10 in LPS-activated monocytes [ 55 ]. Adiponectin seems to promote the differentiation of naïve T cells into Th17 cells, contributing to synovial inflammation and bone erosions, which may be mostly dependent on AdipoR1, demonstrated in conditional AdipoR1 knockout models [ 56 ]. Other cell types such as chondrocytes, endothelial cells, and lymphocytes also showed a pro-inflammatory response to adiponectin [ 12 , 24 ], suggesting a mainly pro-inflammatory effect of adiponectin locally within the affected joints ( Figure 1 ).…”
Section: Adipokines In Autoimmune Rheumatoid Arthritismentioning
confidence: 99%
“…However, recently Zhang et al. reported that Th17 cell differentiation is suppressed in AdipoR1-deficient mice ( 69 ), suggesting an enhancing role of AdipoR1 for the differentiation of Th17 cells. Although this apparently seems contradict with previous reports ( 11 13 ), this is probably because signaling through AdipoR2 is enhanced in the absence of AdipoR1.…”
Section: Discussionmentioning
confidence: 99%
“…Their unique molecular determinants are upregulated expression of Traf6 and Eomes and activation through the pathway Pu.1-Traf6-NF-κB [ 109 ]. Th17 cells are characterized by the molecular determinants mir26 [ 110 ], HIF-1, pyruvate kinase M2 (PKM2) [ 111 ] and adiponectin [ 112 ]. Treg cells (Foxp3+) have a suppressive function with respect to autoimmune reactivity [ 113 ].…”
Section: At Work For the Immune Systemmentioning
confidence: 99%
“…T cell metabolism also plays an important role in diseases like autoimmunity (e.g., systemic lupus erythematosus (SLE), graft-versus-host disease (GvHD), and rheumatoid arthritis (RA)) [ 4 ]. Th17 cells ( Table 3 ) were recently demonstrated to play an important role in RA via microRNA 26 [ 109 ], pyruvate kinase M2 (PKM2) [ 112 ], and the hormone adiponectin [ 116 ]. (5) Over-reactivity.…”
Section: At Work For the Immune Systemmentioning
confidence: 99%